2023
DOI: 10.1021/acsenergylett.3c01256
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality Implications of Using Ammonia as a Renewable Fuel: How Low Can NOx Emissions Go?

Srujan Gubbi,
Renee Cole,
Benjamin Emerson
et al.

Abstract: In addition to their lifecycle carbon emissions, another important issue with decarbonized energy pathways is their air quality, water, or land use implications. This paper considers the air quality issue for ammonia combustion. When directly combusting ammonia, reactions of its N atom with atmospheric oxygen lead to NO x emissions that are O­(103) ppm, 2 orders of magnitude higher than EPA limits or the amount emitted by current natural-gas-fired technologies. In order to provide guidance to policymakers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This suggests working with H 2 concentrations in fuel mixtures lower than the present one. Further reduction of NO can be achieved by increasing the nominal pressure [27]. This will be the aim of future work.…”
Section: Analysis Of the Combustion Modesmentioning
confidence: 96%
See 1 more Smart Citation
“…This suggests working with H 2 concentrations in fuel mixtures lower than the present one. Further reduction of NO can be achieved by increasing the nominal pressure [27]. This will be the aim of future work.…”
Section: Analysis Of the Combustion Modesmentioning
confidence: 96%
“…Numerical studies suggest that optimizing the equivalence ratio in the first (rich) combustion stage is essential for achieving low emissions at the outlet [26]. Furthermore, chemical kinetics investigations demonstrated that using a staged combustion (consisting of a rich stage, followed by a relaxation stage before the final lean stage) coupled with high-pressure conditions (>20 bar), it is fundamentally possible to achieve NO x emissions as low as in natural gas turbines [27].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the Toyota Corporation presented an ammonia engine suitable for passenger cars developed in collaboration with the Chinese car manufacturer GAC [54]. Although environmental concerns may arise regarding NOx levels during ammonia combustion, the technology is expected to meet regulation standards by performing suitable changes in combustion equivalence ratio, combustion chamber pressure, and applying emission control strategies [55].…”
Section: Return Of Ammonia As Alternative Fuelmentioning
confidence: 99%
“…Gubbi et al [55] performed a numerical study, evaluating the NO emission expected from ammonia combustion by changing combustor pressure and residence time. These authors indicated that current NOx regulation limits can be complied with, by changing operating parameters and allowing higher residence time in the combustor.…”
Section: Gas Turbinesmentioning
confidence: 99%
“…The use of ammonia in the power sector is driven by the fact that ammonia is a “carbon-free fuel” as it contains only nitrogen and hydrogen . When ammonia is thermally combusted or electrically converted there is no resulting carbon dioxide, although NOx must be managed . The use of ammonia in the agriculture sector is for fertilizer production. , Ammonia is also a widely used nitrogen-based building block for many other chemicals (e.g., nylons, refrigerants, explosives, poly­urethanes).…”
mentioning
confidence: 99%